BIOLOGIA REPRODUTIVA E DIVERSIDADE GENÉTICA EM Campomanesia xanthocarpa O. BERG (MYRTACEAE) - Homczinski, Isabel (2021)
The development of actions that promote the conservation and management of a species requires an understanding of its reproductive behavior, genetic structure, as well as information on its initial growth, seedling production, selection of seed trees, seed viability and factors that affect its growth. The objective of this research was to evaluate the phenology and reproductive biology, genetic variability and diversity, seed storage, in vitro culture and initial development of Campomanesia xanthocarpa. For the study of phenological activity and intensity, observations were carried out on 34 seed trees in monthly visits between 2016 and 2019 in the Irati National Forest (FLONA of Irati), Parana state, and subsequently correlated with meteorological data. To evaluate the floral and fruiting biology, 50 buds, flowers, and fruits from an urban area tree in Irati, Parana state were used, with monitoring on alternate days, from bud formation to spontaneous fruit abscission. The biometrics of the floral pieces and fruits were carried out during their development, evaluation of the stigma receptivity and the viability of the pollen grains. For the analysis of genetic diversity, the leaf tissues of 80 individuals present in the FLONA of Irati were analyzed with microsatellite markers, and the parameters of diversity and the interpopulation spatial genetic structure (SGS) were evaluated. To analyze the genetic variability, a field progeny test was installed in a randomized block design, with nine treatments (progenies), three blocks and four plants per plot spaced 9 m², and the genetic parameters of the biometric variables were evaluated with 2.9 years old. To evaluate the biometrics and the initial development, 10 seed trees were selected in the FLONA of Irati, for collection of fruits and installation of a progeny test. The progenies were evaluated in relation to emergence, survival, and seedling biometry, in a greenhouse and under full sun in a nursery. In the field, the progenies of nine matrices were evaluated for the increase of biometric variables in a seasonal period for two years. To evaluate seed storage, fruits from 14 seed trees from two counties in Parana state were collected. The seeds were processed, disinfected, and stored at 6 ºC, in polypropylene falcon tubes, containing autoclaved water, until use. The germination on Germitest paper and its viability were evaluated by the tetrazolium test at 0, 30, 60 and 90 days of storage. For in vitro cultivation, seed germination, seedling emergence and acclimatization were evaluated in two culture medium (MS and WPM) in four concentrations of activated charcoal (0, 1, 2 and 3 g L-1). Another experiment was carried out involving stored (30 days) and fresh seeds (0 days), cultivated in WPM medium with 1 g L-1 of activated charcoal, in four concentrations of gibberellic acid (GA3) (1.0, 1.5, 2.0 and 2.5 mg L-1). The reproductive phenology ranged between the years evaluated due to the influence of climatic variables on the phenological acivity and intensity. Flower development lasted around 20 days from bud formation to flower senescence. Stigma receptivity started at the balloon stage, extending until the beginning of flower senescence, and the pollen grains reached the maximum germination in vitro (73.13%), 20 hours after their incubation. Fruit formation took 49 days to complete, from flower senescence to spontaneous fruit abscission. For the population studied, the average observed and expected heterozygosities means were Ho = 0.478 and He = 0.717. The average fixation index (F) was 0.333, inferring that the population may be in the process of inbreeding. The SGS suggested a minimum distance between 50 m for seed collection and selection of seed trees. For the quantitative genetic analysis, it was found that the average heritability is moderate to medium to high, and the traits height and crown diameter stand out in relation to the other variables and can be used in the selection of superior genotypes. The choice of seed trees influenced the percentage of emergence, biometry, and survival of the progenies in a greenhouse, full sun nursery and in the field. The season influenced the increase in biometric variables, with a greater increase in the warm seasons (spring and summer). The germination test revealed loss in germinability of C. xanthocarpa seeds after storage, decreasing from 80% without storage to 17% after 90 days. Germination was 62% up to 60 days, while seed viability was 57%. By the tetrazolium test, the correlation between germination and seed viability was 80%. The species seeds can be stored in polypropylene containers, with autoclaved deionized water at 6 ºC for up to 60 days. The most suitable culture medium for the in vitro cultivation of zygotic species embryos was the WPM medium. The 1 g L 1concentration of activated charcoal was the most suitable for emergence, and the 3 g L-1 concentration for seedling growth. GA3 concentrations from 2.75 to 4.37 mg L-1 were suggested by quadratic regression for the in vitro growth of seedlings from seeds with or without storage. The most critical phase of acclimatization is the second phase (transplanting the glass with a sterilized substrate to the tubes), which must be kept in mini greenhouses with controlled temperature and humidity, in a substrate containing organic fertilizer. This research contributes to a better knowledge of the species regarding its reproductive system, genetic structure and variability, seedling production and initial field development.